106k views
0 votes
Use substitution to solve.Solve the first equation for y and substitute it into the second equation. The resulting equati

Use substitution to solve.Solve the first equation for y and substitute it into the-example-1
User Jao
by
5.7k points

1 Answer

3 votes

The first equation is given as,


\begin{gathered} 2X^2\text{ = 5 +Y} \\ Y\text{ = }2X^2\text{ - 5\_\_\_\_\_\_\_(1)} \end{gathered}

The second equation is given as,


4Y\text{ = }-20\text{ }+8X^2_{_{_{_{}}}}\text{ \_\_\_\_\_\_\_\_\_(2)}

Substituting equation ( 1 ) in equation (2),


4(\text{ }2X^2\text{ - 5) = }-20\text{ }+8X^2_{_{_{_{}}}}\text{ }

Simplifying further,


8X^2-20\text{ = -20 + }8X^2

Thus the required answer is


8X^2-20\text{ = -20 + }8X^2

User Avishka Dambawinna
by
5.5k points